Exam warriors - Modi, Narendra (Haryana Penguin random house, 2018)
The new and enhanced edition of Exam Warriors by Narendra Modi is not only an inspiring book for students but also for their parents and teachers. Written in a fun and interactive style, with illustrations, activities and yoga asanas, this book will be a friend in acing exams and facing life.
Keywords: Hatha yoga for children; Homework; Study skills